Fundamental Concepts, Knowledge Gaps and Key Concerns Relating to Welfare and Survival of Stranded Cetaceans - Rebecca M. Boys; Ngaio J. Beausoleil; Matthew D. M. Pawley; Katherine E. Littlewood; Emma L. Betty; Karen A. Stockin (Diversity, 2022)
Wildlife management can influence animal welfare and survival, although both are often not explicitly integrated into decision making. This study explores fundamental concepts and key concerns relating to the welfare and survival of stranded cetaceans. Using the Delphi method, the opinions of an international, interdisciplinary expert panel were gathered, regarding the characterisation of stranded cetacean welfare and survival likelihood, knowledge gaps and key concerns. Experts suggest that stranded cetacean welfare should be characterised based on interrelated aspects of animals’ biological function, behaviour, and mental state and the impacts of human interventions. The characterisation of survival likelihood should reflect aspects of stranded animals’ biological functioning and behaviour as well as a 6-month post-re-floating survival marker. Post-release monitoring was the major knowledge gap for survival. Welfare knowledge gaps related to diagnosing internal injuries, interpreting behavioural and physiological parameters, and euthanasia decision making. Twelve concerns were highlighted for both welfare and survival likelihood, including difficulty breathing and organ compression, skin damage and physical traumas, separation from conspecifics, and suffering and stress due to stranding and human intervention. These findings indicate inextricable links between perceptions of welfare state and the likely survival of stranded cetaceans and demonstrate a need to integrate welfare science alongside conservation biology to achieve effective, ethical management at strandings.